Sesamin Exerts an Antioxidative Effect by Activating the Nrf2 Transcription Factor in the Glial Cells of the Central Nervous System in Drosophila Larvae - Akihiro Tsuji; Eiji Kotani; Yoshihiro H. Inoue (MDPI AG, 2024)
Sesame seeds are abundant in sesamin, which exerts health-promoting effects such as extending the lifespan of adult Drosophila and suppressing oxidative stress by activating the Nrf2 transcription factor. Here, we investigated whether sesamin activated Nrf2 in larval tissues and induced the expression of Nrf2 target genes. In the sesamin-fed larvae, Nrf2 was activated in the central nervous system (CNS), gut, and salivary glands. The ectopic expression of Keap1 in glial cells inhibited sesamin-induced Nrf2 activation in the whole CNS more than in the neurons, indicating that sesamin activates Nrf2 in glia efficiently. We labeled the astrocytes as well as cortex and surface glia with fluorescence to identify the glial cell types in which Nrf2 was activated; we observed their activation in both cell types. These data suggest that sesamin may stimulate the expression of antioxidative genes in glial cells. Among the 17 candidate Nrf2 targets, the mRNA levels of Cyp6a2 and Cyp6g1 in cytochrome P450 were elevated in the CNS, gut, and salivary glands of the sesamin-fed larvae. However, this elevation did not lead to resistance against imidacloprid, which is detoxified by these enzymes. Our results suggest that sesamin may exert similar health-promoting effects on the human CNS and digestive tissues.